Sterile Reverse Osmosis Water Combined with Friction Are Optimal for Channel and Lever Cavity Sample Collection of Flexible Duodenoscopes - Alfa, Michelle J.; Singh, Harminder; Nugent, Zoann; Duerksen, Donald; Schultz, Gale; Reidy, Carol; DeGagne, Patricia; Olson, Nancy (Frontiers in Medicine, 2017)
Background/Aims: Simulated-use buildup biofilm (BBF) model was used to assess various extraction fluids and friction methods to determine the optimal sample collection method for polytetrafluorethylene channels. In addition, simulated-use testing was performed for the channel and lever cavity of duodenoscopes. Materials and Methods: BBF was formed in polytetrafluorethylene channels using E. faecalis, E. coli and P. aeruginosa. Sterile reverse osmosis water (RO), and phosphate buffered saline (PBS) with and without Tween80 as well as two neutralizing broths (Letheen and Dey-Engley) were each assessed with and without friction. Neutralizer was added immediately after sample collection and samples concentrated using centrifugation. Simulated-use testing was done using TJF-Q180V and JF-140F Olympus duodenoscopes. Results: Despite variability in the bacterial CFU in the BBF model none of the extraction fluids tested were significantly better than RO. Borescope examination showed far less residual material when friction was part of the extraction protocol. The RO for flush-brush-flush extraction provided significantly better recovery of E.coli (p=0.02) from duodenoscope lever cavities compared to the CDC flush method. Discussion and Conclusions: We recommend RO with friction for flush-brush-flush extraction of the channel and lever cavity of duodenoscopes. Neutralizer and sample concentration optimize recovery of viable bacteria on culture.